Evaluasi Program Tahfidz Al-Qur’an Menggunakan Model CIPP (Context, Input, Process, dan Product) di Yayasan Ponpes Ishlahul Ummah NW Lendang Kejah, Lombok Tengah - Muslimaeni Muslimaeni; Yuni Aulia Putri; Nuhalizah Nuhalizah; Novi Dian Rahmadani; Siti Wahida Hilmi; Candra Candra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to evaluate the implementation of the Al-Qur'an memorization program at the Ishlahul Ummah Nahdlatul Wathan (NW) Islamic Boarding School Foundation, Lendang Kejah Village, Batukliang District, Central Lombok Regency, West Nusa Tenggara, using the CIPP (Context, Input, Process, and Product) evaluation model. This study is motivated by the importance of education based on Al-Qur'an values ​​in shaping the religious character of students amidst the challenges of globalization. This study uses a qualitative approach with an evaluative research type. The research subjects consisted of Islamic boarding school leaders, tahfidz ustaz/ustazah, and students. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions, while the validity of the data was tested through triangulation of sources and techniques. The results of the study indicate that in terms of context, the tahfidz program has been in accordance with the needs of the institution and the vision of Islamic education being implemented. In terms of input, the program is supported by competent teaching staff and a focused curriculum, although facilities and funding are still limited. In terms of process, the program is structured through routine and consistent tahsin (recitation), tahfidz (recitation), murajaah (recitation), and memorization (memorization) activities. In terms of product, the program demonstrates an increase in student memorization achievement, sustainable implementation of activities, and the development of discipline, responsibility, and religious character. Based on these findings, the Quran memorization program at the Ishlahul Ummah NW Islamic Boarding School Foundation is deemed effective, as it achieved the established memorization targets and positively impacted student character development.